Family supportive supervisor behavior and work-family boundary control in teleworkers during a lockdown: Portugal and Pakistan comparison - Carvalho, Vânia Sofia; Imam, Hassan; Chambel, Maria José; Santos, Mariana (Frontiers in Psychology, 2022)
The imposition of telework due to the COVID-19 pandemic brought with it the need for individuals to readjust their work-non-work boundaries. In this crisis situation, individuals' needs to manage these boundaries may have been influenced by contextual factors, such as family-supportive supervisor behaviors (FSSB), and macro-structural aspects, such as the country to which the teleworkers belong. This study tests the mediating effect of boundary control on the relationship between FSSB and satisfaction with life and examines the moderating effect of the country (Pakistan vs. Portugal) on the relationship between FSSB and boundary control. With a sample of 108 Portuguese and 118 Pakistani individuals, the results were analyzed using Process tool. FSSB was found to be important for teleworkers to control their boundaries and satisfaction with life. This control was also seen to contribute to higher levels of life satisfaction. Differences between the two countries were observed: boundary control mediates the relationship between FSSB and satisfaction with life for Pakistani teleworkers. These workers are more dependent on FSSB to exercise boundary control than Portuguese teleworkers. This study highlights the importance of considering contextual factors when implementing telework. Practical implications are discussed.